2005
DOI: 10.1007/s10433-005-0008-7
|View full text |Cite
|
Sign up to set email alerts
|

European patterns of intergenerational financial and time transfers

Abstract: The ageing of the European population is expected to strongly influence both the structure of family relations and the pattern of private transfers between generations. Using data from the Survey of Health, Ageing and Retirement in Europe conducted from the perspective of adults aged 50 and above in ten European countries, we provide an analysis of financial and time transfers, either given or received. Our results show that cash gifts mainly flow to the younger generations, while time transfers are directed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
198
0
15

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(224 citation statements)
references
References 9 publications
11
198
0
15
Order By: Relevance
“…The answer categories that we take into consideration are: When interpreting the respondent"s information on care and help, it is important to consider that in a questionnaire module prior to the general activity question which we use, detailed questions were asked, addressing care and help provided within and outside of the respondent"s household over the past 12 months (cf. Attias-Donfut et al 2005). Respondents who already reported such activities in this "social support" module might not have mentioned help or care provided over the past month to avoid repetition.…”
Section: Measurement Of Volunteer Work Informal Help and Carementioning
confidence: 99%
“…The answer categories that we take into consideration are: When interpreting the respondent"s information on care and help, it is important to consider that in a questionnaire module prior to the general activity question which we use, detailed questions were asked, addressing care and help provided within and outside of the respondent"s household over the past 12 months (cf. Attias-Donfut et al 2005). Respondents who already reported such activities in this "social support" module might not have mentioned help or care provided over the past month to avoid repetition.…”
Section: Measurement Of Volunteer Work Informal Help and Carementioning
confidence: 99%
“…Much of the existing literature on intergenerational financial transfers from parents to their adult children has come to the same conclusion: parents are a non-negligible source of financial support for young adults (Kohli 1999;Attias-Donfut, Ogg, and Wolff 2005). Subsequent research has elaborated on this and shown that transfer behaviour is highly dependent on the circumstances of the parent and the child (Albertini, Kohli, and Vogel 2007;Schenk, Dykstra, and Maas 2010).…”
Section: Intergenerational Transfersmentioning
confidence: 99%
“…In the United States, for example, 17 % of the respondents had received a financial gift or loan from their parents in the 5 years before the 1987-1988 National Survey of Families and Households (excluding help with mortgage payments), and only 4 % had given money to their parents (Eggebeen and Hogan 1990; see also Attias-Donfut et al 2005 andAlbertini et al 2007, for 10 European countries). There are not many signs that state support has replaced family support: on the contrary, most evidence seems to suggest that state support and family support tend to go together (Kohli 1999;Attias-Donfut and Wolf 2000;Motel-Klingebiel et al 2005), although Reil-Held (2006) concluded differently for Germany.…”
Section: Theoretical Backgroundmentioning
confidence: 99%